PENGARUH BELANJA BARANG DAN JASA, BELANJA MODAL, BELANJA PEGAWAI DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN SELATAN - EKA CINDY PANGESTU (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research is done for to find out whether goods and services expenditures,  capital expenditures, employee expenditures, and investments have an effect on Economic Growth in South Kalimantan Province with dependent variable of Economic Growth and the independent variable is Expenditure of Goods and Services,Capital Expenditure, Employee Expenditure and Investment.The data used is time series data that is the period 2006 until 2011. The analysis used is multiple linear regression method.The results of this study indicate that the variables of Capital Expenditures and Employee Expenditures Significant Influence on Economic Growth in South Kalimantan Province, the government's suggestion to overcome the economic slowdown of South Kalimantan is the Expenditure of Goods and Services accompanied by efforts to improve the quality of policy support programs such as increasing the quantity and quality of facilities and infrastructure to increase investor interest to invest so that good impact on economic growth, while the value of determination coefficient of 0.776 this means that together independent variables affect the dependent variable.Keywords: Economic Growth, Capital Expenditure, Employee Expenditure, Goods and Services Expenditure, and Investment.